2015
DOI: 10.3390/nu7085292
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Protein Hydrolysates Improve Insulin Resistance and Decrease Pro-inflammatory Cytokine Gene Expression in Rats Fed a High Carbohydrate-High Fat Diet

Abstract: A high carbohydrate-high fat (HCHF) diet causes insulin resistance (IR) and metabolic syndrome (MS). Rice bran has been demonstrated to have anti-dyslipidemic and anti-atherogenic properties in an obese mouse model. In the present study, we investigated the beneficial effects of rice bran protein hydrolysates (RBP) in HCHF-induced MS rats. After 12 weeks on this diet, the HCHF-fed group was divided into four subgroups, which were orally administered RBP 100 or 500 mg/kg, pioglitazone 10 mg/kg, or tap water for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…Both glucose and insulin are potent factors that are involved in inducing the transcription of key enzyme genes in glycolysis and de novo lipogenesis [34]. It has been found that rice bran derivatives reduce plasma and liver lipids, whereas protein hydrolysates from rice bran improve insulin and leptin sensitivity in high-fat diet-induced metabolic syndrome in hamsters [6, 14]. Insulin triggers the transcriptions of glycolytic and lipogenic enzymes by activating SREBP-1c and LXRα [35, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both glucose and insulin are potent factors that are involved in inducing the transcription of key enzyme genes in glycolysis and de novo lipogenesis [34]. It has been found that rice bran derivatives reduce plasma and liver lipids, whereas protein hydrolysates from rice bran improve insulin and leptin sensitivity in high-fat diet-induced metabolic syndrome in hamsters [6, 14]. Insulin triggers the transcriptions of glycolytic and lipogenic enzymes by activating SREBP-1c and LXRα [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Enzyme-treated rice bran has been shown to be effective against chronic diseases in rat and mouse models [12, 13]. For instance, a recent study showed that protein hydrolysates from rice bran improved insulin resistance in a mouse model [14]. Emerging evidence of the chronic disease-fighting properties of rice bran has advanced the development of rice bran for human use as a functional food and a dietary supplement [15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the antidiabetic and antidyslipidemic activities of rice bran have been reported in different animal model experiments [15][16][17]. Furthermore, the active components in processed rice bran promote health; indeed, the processing itself adds value to the rice bran [18,19].…”
Section: Fermentationmentioning
confidence: 99%
“…Rodent models have demonstrated its efficacy against chronic diseases when treated with enzymes [27,28]. The effect of protein hydrolysates from RB in improving insulin resistance is one of the best examples in this case [29]. Thus, there is a growing evidence of the potential effects of RB in treating chronic diseases and their application to human health [30].…”
Section: Introductionmentioning
confidence: 99%